Good Laboratory Practice for optimization research. Issue 4 (1st April 2016) - Kendall, Graham; Bai, Ruibin; Błazewicz, Jacek; De Causmaecker, Patrick; Gendreau, Michel; John, Robert; Li, Jiawei; McCollum, Barry; Pesch, Erwin; Qu, Rong; Sabar, Nasser; Berghe, Greet Vanden; et al.
Abstract: Good Laboratory Practice has been a part of non-clinical research for over 40 years. Optimization Research, despite having many papers discussing standards being published over the same period of time, has yet to embrace standards that underpin its research. In this paper we argue the need to adopt standards in optimization research. Building on previous papers, many of which have suggested that the optimization research community should adopt certain standards, we suggest a concrete set of recommendations that the community should adopt. We also discuss how the proposals in this paper could be progressed.